Arctic Ocean ice melt and methane production / O derretimento de gelo no Oceano Ártico e a produção de metano - Antonio Carlos Alencar da Silva; Maria Goretti Sabino Cordeiro; Túlio Cordeiro Aragão (Universidade Estadual de Alagoas, 2017)
The Arctic shows the melting phenomenon of ice, a fusion responsible for climate destabilization from various regions of the earth, caused by the greenhouse effect, causing global warming. It is also the most heated region and wealthiest of the source of methane trapped in ice, which melt provides great issue of increasing gas heating. Exposing environmental Arctic conditions, and the effects caused by global warming, is purpose of this article, using empirical research as a methodology where by observable data capture to the current characteristics of the region, marked by environmental destabilization, demonstrated by phenomena such as Melting earth permanently frozen ice and rocks, the permafrost and thereby produce methane. There is also the appearance of circular areas formed by methane bubbles, the Hotspots, and thermokarst lake arising melting of permafrost thaw. Such phenomena cause changes in the heat exchange between the ocean and the atmosphere that reflects sunlight in summer, and a reduction in the ice-covered area, helping to accelerate the heating of the whole region creating unfavorable conditions for the maintenance of the ecosystem. Around these conditions arise facts, such as oil exploration, as opposed to environmental balance triggering environmentalists and scientists to suspension of holdings and control in greenhouse gas emissions for the planet's balance of warranty